RETRACTED: ACADL Functions as a Tumor Suppressor in Hepatocellular Carcinoma Metastasis by Inhibiting Matrix Metalloproteinase 14 - Guo, Danfeng; Zhang, Xiaodan; Cui, Honglei; Yu, Dongsheng; Zhang, Huapeng; Shi, Xiaoyi; Pang, Chun; Li, Jie; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Oncology, 2022)
High aggressiveness is the main reason for the poor prognosis of hepatocellular carcinoma (HCC) patients. However, its molecular mechanisms still remain largely unexplored. ACADL, a mitochondrial enzyme that facilitates the primary regulated step in mitochondrial fatty acid oxidation, plays a role in HCC growth inhibition. However, the function of ACADL in tumor metastasis is not well elucidated. We found that the reduced expression of ACADL is closely associated with the loss of tumor encapsulation, extrahepatic metastasis, and poor prognosis in HCC patients. Upregulation of ACADL significantly inhibited HCC migration and invasion ability. Whereas knockdown of ACADL markedly enhanced cell invasive capability. Expression of matrix metalloproteinase-14 (MMP14) was negatively associated with the content of ACADL in HCC specimens. MMP14-positive patients with a low expression of ACADL showed worse outcome. Treatment with MMP14 agonist reversed the inhibitory effect of ACADL on HCC metastasis. In addition, ACADL negatively regulated MMP14 expression by inhibiting the STAT3 signaling pathway, as the sustained activation of STAT3 effectively restored the level of MMP14 in ACADL-overexpressed cells. Collectively, these findings disclose that ACADL represses HCC metastasis via STAT3-MMP14 pathway. This study may propose a promising strategy for the precise treatment of metastatic HCC patients.